2002
DOI: 10.1076/apab.110.1.50.911
|View full text |Cite
|
Sign up to set email alerts
|

Are Folliculo-Stellate Cells in the Anterior Pituitary Gland Supportive Cells or Organ-Specific Stem Cells?

Abstract: Folliculo-stellate cells (FS-cells) in the anterior pituitary gland are star-shaped cells and form tiny follicles. FS-cells are positive for S-100 protein and produce many cytokines or growth factors, such as interleukin-6 (IL-6), leukemia inhibitory factor (LIF), basic fibroblastic growth factor (bFGF) and vascular endothelial cell growth factor (VEGF). Therefore, it is generally accepted that FS-cells regulate endocrine cells through these growth factors. FS-cells also exhibit a phagocytotic activity and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 14 publications
4
39
0
2
Order By: Relevance
“…Inoue and co-workers reported that skeletal muscle cells could differentiate from FS cells when a pituitary gland was transplanted under the kidney capsule (34). They confirmed this finding in vitro by showing the differentiation of Tpit/F1 cells into striated muscle cells (35).…”
Section: New Approaches For Old Questionssupporting
confidence: 69%
See 3 more Smart Citations
“…Inoue and co-workers reported that skeletal muscle cells could differentiate from FS cells when a pituitary gland was transplanted under the kidney capsule (34). They confirmed this finding in vitro by showing the differentiation of Tpit/F1 cells into striated muscle cells (35).…”
Section: New Approaches For Old Questionssupporting
confidence: 69%
“…A number of papers have recently provided evidence, although only circumstantially, for a role of FS cells as adult stem cells in the anterior pituitary (34,37). Horvath & Kovacs (37) demonstrated that in a large series of adenomatous and non-tumorous human pituitaries, immunoreactivities to S-100 and GFAP were strongest in newly formed follicles, the older microcysts being immunonegative.…”
Section: New Approaches For Old Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact function of these S100 positive non-endocrine cells of the pituitary is not fully appreciated yet. They have been reported to be a major source of several paracrine factors of the pituitary to form a network that facilitates the synchronization of the pituitary gland or to represent a group of progenitor cells with the potential to differentiate into specialized endocrine cells (Allaerts et al 1990, Renner et al 1996, Stojilkovic 2001, Inoue et al 2002. Folliculostellate cell lines derived from rat, mouse, and human anterior pituitaries have been characterized in recent years and experiments with these cells are beginning to shed some light into the function of this cell type (Inoue et al 1992, Danila et al 2000b, Bilezikjian et al 2003.…”
Section: Local Pituitary Actions Of Follistatinmentioning
confidence: 99%